(untitled) (Perner’s Contacts, 2012)
This paper deals with the problematic localization the position of rolling stock within the model of railway network. Primarily are described current systems mainly systems using the GNSS technology. The article also focuses on the design of a railway network model by using Oracle Network Data Model technology and own visualization by using MapViewer technology. Localization the position is verified by using computer simulation.